The fission yeast ortholog of the coregulator SKIP interacts with the small subunit of U2AF - Ambrozková, M; Půta, F; Fuková, I; Skruzný, M; Brábek, J; Folk, P (Biochemical and biophysical research communications, 2001)
The mode of action of transcriptional coregulators may involve the recruitment of spliceosome components. Using the two-hybrid screen, we examined the interaction partners of spSNW1, the S. pombe ortholog of the human coregulator SNW1/SKIP/NCoA-62, and found it to interact with the small subunit of the splicing factor U2AF (spU2AF23). The interaction involves the C-terminal parts of spU2AF23 and spSNW1. Tagged variants of both proteins were expressed in S. pombe and the interaction was proved by coprecipitation in nuclear extracts. This interaction would explain the finding of SKIP in nuclear speckles (Mintz, P. J., et al., EMBO J. 18, 4308-4320, 1999) and in reconstituted spliceosomes (Neubauer, G., et al., Nat. Genet. 20, 46-50, 1998). We deleted the spSNW1 gene in the diploid strain and demonstrated that spSNW1 is an essential gene in S. pombe.
Keywords: Ribonucleoproteins; Transcriptional Activation; Cell Cycle; Splicing Factor U2AF; sestřihový faktor U2AF; buněčný cyklus; Two-Hybrid System Techniques; aktivace transkripce; Saccharomyces cerevisiae; techniky dvojhybridového systému; molekulární sekvence - údaje; Schizosaccharomyces; Molecular Sequence Data; jaderné proteiny; Nuclear Proteins; ribonukleoproteiny